Integrated Analysis of the m6A-Related lncRNA Identified lncRNA ABALON/miR-139-3p/NOB1 Axis Was Involved in the Occurrence of Lung Cancer - Liu X (Dove Medical Press, 2021)
Xinhong Liu,1– 4,* Xin Zuo,5,* Lijun Ma,1– 4 Qin Wang,1– 4 Lilan Zhu,1– 4 Li Li,1– 4 Xin Zhao2– 4 1College of Biological and Chemical Engineering, Chongqing University of Education, Chongqing, People’s Republic of China; 2Chongqing Collaborative Innovation Center for Functional Food, Chongqing University of Education, Chongqing, People’s Republic of China; 3Chongqing Engineering Research Center of Functional Food, Chongqing University of Education, Chongqing, People’s Republic of China; 4Chongqing Engineering Laboratory for Research and Development of Functional Food, Chongqing University of Education, Chongqing, People’s Republic of China; 5Department of Gastroenterology, The Sixth People’s Hospital of Chongqing, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xin ZhaoChongqing Collaborative Innovation Center for Functional Food, Chongqing University of Education, Xuefu Main Street 9, Chongqing, 400067, People’s Republic of ChinaTel +86-23-62653650Email zhaoxin@cque.edu.cnBackground: Lung cancer has the characteristics of early metastasis, high recurrence, and high mortality rate despite emerging advances in diagnostic. Early diagnosis can significantly improve the patient’s chances of cure and survival.Purpose: This study aimed to identify and assess a prognostic lncRNA/miRNA/gene signature in patients with lung cancer.Methods: Pearson correlation analysis, univariate Cox analysis and LASSO Cox analysis were used to construct a lung cancer prognostic risk model based on m6A-related lncRNA. The interaction between lncRNA-miRNA-gene was verified by luciferase reporter gene experiment.Results: The Pearson correlation analysis determined that 1655 lncRNAs significantly correlated with the expression of m6A genes. A lung cancer prognostic risk model, including 14 m6A-related lncRNAs, was constructed through univariate Cox analysis and least absolute shrinkage and selection operator (LASSO) Cox analysis. ABALON was identified as the key lncRNA through cluster analysis and gene expression difference analysis.Conclusion: It was experimentally verified that ABALON acted as a competing endogenous RNA by sponging miR-139-3p and indirectly regulated the expression of NOB1. This study provided a new biological target for the early diagnosis of lung cancer and a new direction for studying the mechanism of lung cancer.Keywords: lncRNA, lung cancer, miRNA, N6-methyladenosine, prognostic biomarker